Co-adsorption capabilities and mechanisms of bentonite enhanced sludge biochar for de-risking norfloxacin and Cu2+ contaminated water. (July 2022) - Cao, Xuewen; Meng, Zhaofu; Song, En; Sun, Xiuxian; Hu, Xiaolong; Wenbin Li,; Liu, Ze; Gao, Shuai; Song, Bing
Abstract: Various bentonite-sludge biochar composites were fabricated by a sequence of loading and pyrolysis for the simultaneous removal of norfloxacin (NOR) and copper (Cu 2+ ) from an aqueous solution. The morphology and characteristics of obtained composites were reflected through cation exchange capacity (CEC), BET specific surface area (SBET ), SEM, XRD, FTIR and XPS. The isothermal adsorption results showed that Sips adsorption model fitted better for the adsorption of NOR and Cu 2+ during co-adsorption. The theoretical maximum adsorption capacity of BT:2 SB (the mass ratio of bentonite to sludge is 1:2) for NOR and Cu 2+ was 89.36 mg g −1 and 104.10 mg g −1 at 25 °C in the co-adsorption system. The thermodynamic results showed the capture of NOR and Cu 2+ was spontaneous, accompanied by an endothermic reaction with different randomness. In the co-adsorption system, the two were antagonistic to each other due to competition for the adsorption sites of hydroxyl, carboxylic acid and negatively charged provided by bentonite-sludge biochar. This study suggests that using natural mineral as a pyrolysis improver for sludge biochar can product the value-enhanced biochar for simultaneous removal of antibiotic and metal contaminants. Graphical abstract: Image 1 Highlights: Bentonite enhanced sludge biochar was fabricated by one-pot pyrolysis method for de-risking norfloxacin and Cu 2+ wastewater. The optimal ratio of bentonite to sludge was 1:2 for co-adsorption norfloxacin and Cu 2+ . The bentonite-sludge biochar composites are efficient and economic materials for environmental remediation.